Depressed recovery of subendocardial perfusion in persistent heart failure after complete revascularisation in diabetic patients with hibernating myocardium. Issue 10 (22nd December 2008) - Mizuno, R; Fujimoto, S; Saito, Y; Nakamura, S
Abstract : Objectives: To investigate the relation between myocardial perfusion and heart failure (HF) status after revascularisation in patients with HF due to hibernating myocardium (HM) in diabetic and non-diabetic subjects. Methods: 31 diabetic and 33 non-diabetic subjects with HF due to HM, who were already scheduled for complete revascularisation, were studied. Before and after revascularisation, left ventricular function and regional perfusion in subendocardial and subepicardial portions of the left ventricular wall were evaluated. Results: Before revascularisation, left ventricular function and regional perfusion were similar in diabetic and non-diabetic subjects. At 6 months after revascularisation, subepicardial perfusion was markedly improved both in diabetic and non-diabetic subjects. However, subendocardial perfusion was markedly improved only in non-diabetic subjects and was little changed in diabetic patients. Thus, subendocardial perfusion was much lower in diabetic than non-diabetic subjects. Left ventricular function was improved more in non-diabetic than in diabetic subjects. Persistent HF was found much more often in diabetic than non-diabetic subjects. At multivariate analysis, subendocardial perfusion at 6 months independently contributed to persistent HF. Conclusions: This study describes the intramural heterogeneity of recovery of myocardial perfusion with depressed improvement in the subendocardial portion and its relation with persistent HF after complete revascularisation in diabetic patients with HF due to HM.